Entrepreneurship Education For Sustainable Development, Opportunities And Challenges In Indonesia - Rusdiaman Rauf; Abd. Azis (BJRM (Bongaya Journal of Research in Management), 2026)
Entrepreneurship education has emerged as an important component in encouraging sustainable development, especially in developing countries such as Indonesia. This article aims to explore the opportunities and challenges associated with entrepreneurship education for sustainable development in the Indonesian context. The study uses a qualitative approach, utilizing in-depth interviews with key stakeholders, including policymakers, educators, and entrepreneurs. These findings reveal that entrepreneurship education in Indonesia has great potential to encourage sustainable development by fostering innovative and socially responsible entrepreneurs. However, the study also identified several challenges, such as the need for better integration of sustainability principles into entrepreneurship curricula, limited access to funding and resources for sustainable startups, and a lack of collaboration between educational institutions and industry. This paper presents a comprehensive framework for strengthening entrepreneurship education for sustainable development in Indonesia. The framework highlights the importance of aligning educational programs with the United Nations Sustainable Development Goals, fostering public-private partnerships, and promoting experiential learning opportunities that emphasize sustainable business practices. In addition, the study recommends policy interventions to support sustainable entrepreneurship, such as tax incentives, access to financing, and the establishment of incubation centers.